Titanium dioxide nanoparticles induce neurotoxicity through PI3K/Akt-mediated mitochondrial apoptosis - Zhibing Zhang; Yanyan Fang; Shuang Chen; Kun Peng; Xiang Gao; Jingdong Zhang; Qinyu Peng; Shangqi Sun; Danhao Xia; Lanxia Meng; Qihu Zhu; JiaHong Lu; et al. (Toxicology, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Prediction of honey adulteration using machine learning-assisted OIRD - Shanzhe Zhang; Shunyi Li; Hao Yang; Enhao Tang; Xiaorong Sun; Yuan Gao; Cuiling Liu; Kun Zhao (Food Bioscience, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

A novel oral prodrug (CK301) for effusive feline infectious peritonitis: An open-label study evaluating dose optimization and therapeutic efficacy - Zihang Ma; Siying Li; Shenghe Sun; Zhuofan Gao; Xin Li; Jinping Chen; Zhen Wang; Shizhe Liu; Chuangqi Sun; Yongzhong Xiong; Kun Jia; Linghua Hao; et al. (Veterinary Microbiology, 2026)

First report of mass mortality in post-metamorphosis Magallana gigas associated with OsHV-1 in China: epidemiological and genomic characterization - Bo-Wen Huang; Xiang Zhang; Tao Xu; Yi-Tao Zhang; Xiao-Ai Li; Lei Gao; Ning Kong; Ming-Kun Liu; Tao Yu; Hui-Gang Kang; Chong-Ming Wang; Chang-Ming Bai (Journal of Invertebrate Pathology, 2026)

Ni regulated LaMnO3 for selective nitrite to ammonia electroreduction - Kun Lang; Yuanyingxue Gao; Panzhe Qiao; Xudong Xiao; Mingyang Liu; Bin Wang; Xinrui Li; Wei Wu; Jingping Ge; Huiyuan Meng; Baojiang Jiang (Journal of Hazardous Materials, 2026)

Short-term nutrient addition and grazing reveal divergent effects on N and P limitations in a desert steppe - Qian Liu; Haina Hu; Kun Zhao; Hui Gao; Chunxue Han; Haigang Li (Agriculture, Ecosystems & Environment, 2026)

When water turns toxic: how climate change drives cyanotoxin biosynthesis-A mechanistic review - Ayesha Shakoor; Yanyan Zhang; Yimeng Li; Kun Shan; Chaorui Yan; Yang Li; Xiaoyan Tang; Yingjie Wu; Lijun Hou; Xuesong Gao (World Journal of Microbiology and Biotechnology, 2026)

Long-term subsoiling enhanced soil organic carbon sequestration via macropore optimization and iron-aluminum oxides enrichment - Yecheng Zhang; Fiston Bizimana; Kun Han; Xiaohan Duan; Shaobo Wang; Jingyi Shao; Xinkun Liu; Qisong Gao; Xianfeng Zhang; Keqiang Li; Ling Liu; Huifang Han (Soil and Tillage Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The TORC-SnRK Axis: An Integrative Signaling Framework Balancing Growth and Stress Responses in Plants - Gao-Jia Yan; Qiu-Yan Yang; Yu-Song Liu; Jian Li; Hui Xue; Sheng Luan; Kun-Lun Li (Molecular Plant, 2026)

Synergistic gellan gum/flaxseed gum composite enhances freeze-thaw stability of soy isolate protein emulsion gels - Junxian Zhao; Yuan Xu; Atif Arshad; Mingru Zhang; Yue Sun; Xueling Li; Kun Gao; Jin Liang (Food Chemistry, 2026)

Coordinated cofactor and peroxide self-circulation enables sustainable synthesis of α, ω-dicarboxylic acids - Kun Cao; Yishu Li; Xiao Ma; Zhen Gao; Bin Wu; Anni Li; Xujian Wang; Bingfang He; Gerhard Schenk (Chemical Engineering Journal, 2026)

BMSC-derived exosomal METTL3 synergizes with Sevoflurane to inhibit ferroptosis in pulmonary ischemia/reperfusion injury by enhancing USP7 N6-methyladenosine modification - Liang Zheng; Xiang-yu Xie; Kun Li; Xiao-feng He; Jiang Shen; Cao Gao (Apoptosis, 2026)

Switchable downward/upward dual-mode evaporator enabled by Marangoni effect: Toward efficient evaporation and salt harvesting from high-salinity brine - Jinmei He; Zongrui Huang; Jiehui Li; Ying Zhang; Ziqi Liu; Yuhang Gao; Kun Xue; Yuanyuan Wang; Xinyi Tian; Mengnan Qu (Chemical Engineering Journal, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Aqueous biphasic systems based on dual deep eutectic solvents for simultaneous extraction and targeted partitioning of bioactive compounds from Cinnamomum cassia - Lili Zhang; Zhanghui Xie; Yuya Liu; Jianzhao Xu; Jipeng Liang; Mengfan Li; Lili Hu; Kun Hu; Jing Gao (Food Chemistry, 2026)

Structure-driven bioaccumulation of legacy and emerging PFAS across freshwater biota and tissues: Implications for dietary exposure and age-specific risks - Wu Wen; Qinghao Wang; Lijuan Gao; Jingling Liu; Bin Sun; Nannan Chen; Kun Bao; Li Ling; Xinghui Xia (Environmental Pollution, 2026)

Graphitization of marine kerogen and its effects on nanopores and adsorption performance - Guangming Meng; Xianming Xiao; Haifeng Gai; Yanming Zhao; Yijie Xing; Kun Zhang; Yu Liu; Qin Zhou; Tengfei Li; Wei Liu; Peng Cheng; Ping Gao (Science China Earth Sciences, 2026)

Isolation of new sesquiterpene glycosides from Dendrobium nobile and evaluation of their antitumor activity - Gu Min; Shu-chang Gao; Xiao-li Ma; Xiao-peng Huang; Yi-wei Chen; Xu-liu Shi; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Decoding gibberellin–strigolactone interaction networks in cereal crops toward a next-generation Green Revolution - Jie Hu; Yunzhe Wu; Shuang Zhang; Qiaoling Zhang; Zhe Chai; Dan Li; Danlin Zhao; Binghui Wu; Xiuhua Gao; Xueying Liu; Kun Wu; Xiangdong Fu (Molecular Plant, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Research on three-dimensional forward modeling and response characteristics for anisotropic resistivity based on multichannel electrodes - Jun-kai Yu; Fu-yu Jiang; Jiong Ni; Pei-xuan Qiao; Li-Kun Gao (Applied Geophysics, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Development of global diffusion filling model for voids filling of Digital elevation models (DEMs) - Guoqing Zhou; Kun Li; Cong Li; Hanwen Gao; Ertao Gao; Xiang Zhou; Jiasheng Xu; Jianjun Chen (International Journal of Remote Sensing, 2026)

Research on Intelligent Identification of Dike Hidden Hazards Based on GprMax Forward Modeling and YOLOv11 Deep Learning: A Case Study of Wenzaobang River in Shanghai - Fu-yu Jiang; Run Han; Li-kun Gao; Jiong Ni; Jun-kai Yu; Xiao-yu Xu (Applied Geophysics, 2026)

Transgenerational Effects of Elevated Temperature on Life History and Lambda-Cyhalothrin Sensitivity in Cydia Pomonella - Kang-Wu Zheng; Zi-Han Wei; Zi-Nan Xia; Bo-Kun Wang; Ping Gao; Yu-Ting Li; Xue-Qing Yang (Neotropical Entomology, 2026)

Quantitative Assessment of Rock Bolt Bond Length on Load-Bearing Capacity and Failure Mechanisms - Chuanming Li; Jiankui Bai; Ruimin Feng; Jucai Chang; Wenbao Shi; Xiang Gao; Kun Wang; Zhengrong Zhang; Bochao Nie; Chuan Li; Jianguo Cao; Qinghua Han (Rock Mechanics and Rock Engineering, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Psychromicrobium ferritrahens sp. nov., A Novel Actinobacterium Isolated from Decayed Wood in Shizong County, China - Lin-Bo Zhang; Jiang-Yuan Zhao; Yong-Jie Zeng; Hong-Bo Zha; Lin Gong; Pei-Wen Yang; Zhang-Gui Ding; Ming-Gang Li; Shun-Bo Gao; Le-Le Li; Shu-Kun Tang (Current Microbiology, 2026)

A multifunctional MOF-818-based nanozyme for synergistic therapy of hepatic steatosis via dual-channel lipid regulation and ROS scavenging - Haonan Zhang; Huili Zhao; Yingying Liu; Tuo Ji; Yuzhi Gao; Guohua Chen; Yuwei Bian; Zhiwen Zhao; Kun Yu; Xinwei Li; Xuzhu Gao (Chemical Engineering Journal, 2026)

Metabolic reprogramming of Bacillus subtilis for surfactin: Maximizing titer/yield/productivity and tailoring C14/C15 homologue proportions - Ling Gao; Kun Du; Yilang Zhou; Chenyu Li; Yumeng Su; Xiaole Xia (Chemical Engineering Journal, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Shuyu capsule improves estrous cycle-dependent depression-like behavior in premenstrual dysphoric disorder (PMDD) mice by increasing GABAergic neuronal activation and downregulating GABAAR δ subunit expression in the dorsal periaqueductal gray (dPAG) region - Jialing Xu; Kun Liu; Yaru Cui; Hao Zhang; Xinyu Wang; Minghui Hu; Zifa Li; Peng Gao; Wei Liu; Mingqi Qiao; Wenqiang Cui; Xiwen Geng; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Different detoxification strategies of fruit borers adaptation to quercetin - Bing Bai; Huan-Juan Zhao; Bo-Kun Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Superefficient PM0.3 filtration and high-selectivity CO2 adsorption by MOF-activated poly(lactic acid) nanofibers - Li-Ning Dong; Cunmin Wang; Le Bao; Kun Yu; Yuzhen Hou; Xinjian He; Mengbao Fan; Shenghui Zhang; Shu-Gui Yang; Jiefeng Gao; Huan Xu (Chemical Engineering Journal, 2025)

A 3D porous AgNWs/graphene/PDMS sensor enabling multifunctional applications for gesture recognition and health monitoring - Li Wang; Yaxin Wang; Shaoqi He; Jiahong Wen; Qifeng Du; Yongjun Zhang; Wenting Zhang; Renxian Gao; Kun Zhang; Rufei Cui; Fengyi Zhang; Xiqiang Zhong; et al. (Chemical Engineering Journal, 2025)

Bi-modified octahedral cuprous oxide with exposed high-active surface for Fenton-like catalytic degradation of complex polluted water - Tian Gao; Zhigang Hu; Kun Lei; Jianfeng Bao; Jinghua Li (Journal of Environmental Management, 2025)

Engineering robust, hierarchical, and biodegradable cellulose foams for smart packaging - Aijun Xie; Haishun Du; Sonali Mohapatra; Kun Liu; Jisheng Yang; Jee-Hwan Oh; Mohan Li; Yumeng Zhang; Mengge Gao; Sundaram Gunasekaran; Xuejun Pan (Chemical Engineering Journal, 2025)

Riding through the heat: Assessing heat health risk of cycling based on diurnal temperature and shared-bike big data - Kun Zeng; Feng Gao; Yihuan Peng; Chang Liu; Wangyang Chen; Guanyao Li (Applied Geography, 2025)

Global Change Alters the Abundance and Community Structure of Arbuscular Mycorrhizal Fungi and Influences Plant Mycorrhizal Benefit - Ai‐Tian Ren; Meng‐Li Wang; He‐Miao Gao; Bede S. Mickan; Long‐Yi Yuan; Si‐Kun Liu; Shao‐Cong Zhang; Lynette K. Abbott; You‐Cai Xiong; Fei Mo (Global Ecology and Biogeography, 2025)
Aims Arbuscular mycorrhizal (AM) fungi play critical roles in ecosystem services and exhibit sensitivity to global change factors (GCFs). However, the interactive effects of multiple GCFs on AM fungal communities, and whether changes in AM fungal communities have a feedback effect on plant–mycorrhizal benefits under global change remain poorly understood. Location Global. Time Period 1990 – 2022. Major Taxa Studied Arbuscular mycorrhizal fungi; arbuscular mycorrhizal plant hosts. Methods We synthesised 1646 observations of arbuscular mycorrhizal (AM) fungal communities from field experiments to evaluate how manipulated GCFs affect their abundance and community structure and to determine the potential consequences for outcomes of plant–mycorrhizal fungal relationships. Results The interactive effects among GCFs were mainly additive rather than synergistic or antagonistic. AM fungal diversity was not consistently sensitive to the individual effects of GCFs; however, a significant shift in community structure occurred under individual or concurrent GCFs. When multiple factors were imposed simultaneously, their negative effect on AM fungal colonisation was strengthened, while their effects on community structure were diminished. Moreover, plant performance was closely linked to changes in abundance and community structure of AM fungi under GCFs. Experimental duration and environmental variables emerged as the most important predictors of AM fungal responses to GCFs. Conclusions Reordering or replacement of AM fungal species has been identified as the key mechanism driving community responses to GCFs. Our study highlights the need to monitor AM fungal community structure and associated functional consequences for plant communities under ongoing global change.

Harnessing PoSAP, a serum amyloid P component in Japanese flounder (Paralichthys olivaceus) for superior antibacterial immunity in teleost fish - Sheng-han Gao; Jia-qi Sun; Kun-yu Zhao; Gang Li; Jian Zhang; Xue-peng Li (Aquaculture, 2025)

A cranium of “Gazella” nihensis from Pliocene of Qinghai-Tibetan Plateau and the differentiation of early Antilopina - Shi-Qi Wang; Xiao-Yong Zhang; Yi-Kun Li; Xiao-Xiao Zhang; Qi-Gao Jiangzuo (Palaeoworld, 2025)

Switching on PMS activation in standby mode by organic pollutant on single-atom Cu with regulated local coordination geometry - Kun Wang; Jiahao Cui; Yongtao Gao; Lina Li; Wei Qin; Zhenyu Hu; Yubao Zhao (Journal of Environmental Chemical Engineering, 2025)

Evaluation of machine learning applied in membrane-based water desalination: A review - Yuanji Zhang; Jiale He; Dongyang Li; Jing Wang; Qiangqiang Song; Xueling Wang; Junyong Zhu; Xiaoquan Feng; Kun Duan; Xin Gao; Yatao Zhang (Desalination, 2025)

Multi-omic-based classification for identifying optimal neoadjuvant treatment strategies for high-risk early-stage breast cancer - Fei Ji; Xianzhe Chen; Ciqiu Yang; Liulu Zhang; Mei Yang; Jieqing Li; Hongfei Gao; Teng Zhu; Minyi Cheng; Yitian Chen; Hao Peng; Jin Wang; et al. (Science China Life Sciences, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Algal blooms in Lake Taihu: Earlier onset and extended duration - Jiangzhaoxia Chen; Xiaojie Gao; Xiaoke Xu; Chongjing Zhu; Xiaojun She; Debing Kong; Kun Xue; Yao Li (Harmful Algae, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Scrutinising the industrial carbon emissions of China’s Yangtze river economic belt: decoupling efforts and mitigation pathways - Liu Chen; Haixiang Feng; Xiaofeng Gao; Kaijian Li; Luping Qin; Kun Zhou (Environment, Development and Sustainability, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

Removal of aqueous As(Ⅴ) by biochar stabilized green synthesized iron nanoparticles: Optimization, mechanism and DFT insights - Xueping Li; Hong Chen; Kun Rong; Qi Gao; Jianchao Jin; Shilai Yi; Qian Yang; Chunlong Sun; Ruimin Li; Zhenjiang Yin; Zaiwang Zhang (Journal of Environmental Chemical Engineering, 2025)

Prediction of fluidization state in a pulsed gas-solid fluidized bed - Yanjiao Li; Deqi Li; Heng Jiang; Yushan Dong; Zhonglin Gao; Kun Hong; Liang Dong (Chemical Engineering Journal, 2025)

Multi-functional dumbbell DNA probe design and its application in signal amplification cascade -based assay of human immunodeficiency virus - Yan Gao; Yifei Li; Qian Gao; Tao Zhang; Yirui Zhang; Tao Liu; Kun Han (Analytica Chimica Acta, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Corrigendum to “A novel ASGR1-Targeting nanocomplex for mitigating donor liver steatosis” [Chem. Eng. J. 513 (2025) 163089] - Xinwei Li; Yingying Liu; Deshu Dai; Huan Liu; Guangyao Zhang; Lianghao Zhang; Shangheng Shi; Peng Jiang; Bingliang Zhang; Zhiwen Zhao; Xuzhu Gao; Kun Yu; et al. (Chemical Engineering Journal, 2025)

Influence of Principal Stress Orientation on Cyclic Degradation of Soft Clay Under Storm Wave Loading - Chengcong Hu; Feng Gao; Biao Huang; Peipei Li; Zheng Hu; Kun Pan (Journal of Marine Science and Engineering, 2025)
Coastal marine soft clays subjected to long-term storm wave loading often exhibit inclined initial principal stress orientation (α0) and subsequent cyclic principal stress rotation (PSR). These stress states critically influence soil mechanical behavior and failure mechanisms, threatening offshore structural stability. This study employs hollow cylinder apparatus testing to investigate the undrained cyclic loading behavior of reconstituted soft clay under controlled α0 and PSR conditions, simulating storm wave-induced stress paths. Results demonstrate that α0 governs permanent pore pressure and vertical strain accumulation with distinct mechanisms, e.g., a tension-dominated response with gradual pore pressure rise at α0 45°. Rotational loading with PSR significantly intensifies permanent strain accumulation and stiffness degradation rates, exacerbating soil’s anisotropic behavior. Furthermore, the stiffness degradation index tends to uniquely correlate with the permanent axial or shear strain, which can be quantified by an exponential relationship that is independent of α0 and PSR, providing a unified framework for normalizing stiffness evolution across diverse loading paths. These findings advance the understanding of storm wave-induced degradation behavior of soft clay and establish predictive tools for optimizing marine foundation design under cyclic loading.

Anti-inflammatory sesquiterpenoids from Chloranthus japonicus - Wei-Jiao Feng; Pei-Zhi Huang; Li-Mei Zhang; Qian Ma; Hong-Yu Hu; Yue Gu; Ya Li; Kun Gao (Phytochemistry, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

A novel ASGR1-Targeting nanocomplex for mitigating donor liver steatosis - Xinwei Li; Yingying Liu; Deshu Dai; Huan Liu; Guangyao Zhang; Lianghao Zhang; Shangheng Shi; Peng Jiang; Bingliang Zhang; Zhiwen Zhao; Xuzhu Gao; Kun Yu; et al. (Chemical Engineering Journal, 2025)

Effects of anthropogenic activities on soil microbial community structure and methane anaerobic oxidation rate in coastal wetlands of Yellow River Delta, China - Chenmiao Liu; Zihao Wang; Xia Gao; Kun Li; Lei Yu; Jingyu Sun; Hongjie Di; Xiaoya Xu; Qingfeng Chen (Applied Soil Ecology, 2025)

Preparation of high-performance adsorption carbon materials via hydrothermal carbonization of agricultural solid waste-grapevines - Kun Wang; Yulu Yang; Chang Liu; Yanan Li; Chang-Qing Cao; Pei-Gao Duan; Liang Pei; Jia Duo (Journal of Environmental Management, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Mechanism of arsenic regulation of mitochondrial damage and autophagy induced synaptic damage through SIRT1 and protective effect of melatonin in HT22 cell - Xiaoli Zhang; Jing Wang; Shuyuan Li; Kun Chen; Longmei Wang; Chao Feng; Yi Gao; Xiaoyan Yan; Qian Zhao; Ben Li; Jinping Zheng; Yulan Qiu (Chemico-Biological Interactions, 2025)

A theoretical framework for chemical storage tank pool fire domino effect prevention based on inherent safety concepts - Xiaoming Gao; Guohua Chen; Caiyi Xiong; Wei Pu; Kun Hu; Xiaofeng Li; Tao Zeng; Hongpeng Lv; Lixing Zhou; Honghao Chen (Process Safety and Environmental Protection, 2025)

Structural characterization of biohumic acid from Hongshaquan lignite degraded by Bacillus sp. XK1 and its application in the Brassica chinensis L. Growth - Chen Shi; Ya-Kun Wang; Long Yan; Yu-Hong Kang; Guang-Hui Liu; Yong Gao; Jin-Jun Bai; Yan-Jun Li; Ai-Min Wang; Ya-Nan Zhu; Xian-Yong Wei (Fuel, 2025)

Design and Experimentation of Mountain-type Pre-cutting Sugarcane Planter and Its Key Components Based on DEM - Shunsheng Zhang; Xinxin Gao; Gaoyuan Liu; Jiawen Guo; Xiaoyu Li; Kun Yang; Mingchun Li; Kai Liu; Yixun Kong (Sugar Tech, 2025)

CircXPO6 promotes breast cancer progression through competitively inhibiting the ubiquitination degradation of c-Myc - Aiqi Xu; Xi Li; Qiaoting Cai; Ciqiu Yang; Mei Yang; Hongfei Gao; Minyi Cheng; Xianzhe Chen; Fei Ji; Hailin Tang; Kun Wang (Molecular and Cellular Biochemistry, 2025)

Suyin Detoxification Prescription Regulates the Klotho and ERK/NF-κB Signaling Pathways to Alleviate Renal Injury - Lianghui Shu; Li Quan; Yanping Wang; Yanlin Chen; Chen Yong; Fang Tian; Kun Gao; Enchao Zhou (Cell Biochemistry and Biophysics, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Efficiency and transcriptomic analysis reveal the mechanism of fermentation residue biochar and dosage on enhancing food waste high solid bioethanol fermentation - Huimin Zhou; Zhaoxia Wang; Junqiu Jiang; Qingliang Zhao; Lili Li; Qingwei Gao; Xinwen Li; Kun Wang (Journal of Cleaner Production, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Insights into the combustion mechanisms of turpentine oil based on ReaxFF molecular dynamics simulations - Chongchong She; Tiancheng Zhang; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Cobalt-catecholate-functionalized nonwoven alginate fabrics for ultrafast photo-pressure sensing - Tianyi Duan; Junxuan Liang; Kai Liu; Kun Zhao; Wei Gao; Jianxi Li; Kewei Zhang; Song Yang (Chemical Engineering Journal, 2025)

Constructing chromium-tolerance La0.6Sr0.4Co0.2Fe0.8O3-δ cathode for solid oxide fuel cells using entropy-assisted surface engineering - Xu Han; Qi Shao; Kaixin Li; Yuan Gao; Bo Wei; Zimin Cai; Kun Zheng; Peizhong Feng; Zhe Lv; Yihan Ling (Chemical Engineering Journal, 2025)

Adoption of no-tillage alters the pools of SOM with various thermal stability and their chemical composition by changing their sources in Northeast China - Shijie Qin; Yuxin Niu; Xinyue Li; Andrew S. Gregory; Zhangliu Du; Kun Zhu; Tusheng Ren; Weida Gao (Soil and Tillage Research, 2024)

Variations of chloride depletion and its impacts on ozone formation: Case study of a coastal area in Shanghai - Yusen Duan; Yan Liu; Kun Zhang; Li Li; Juntao Huo; Jia Chen; Qingyan Fu; Zongjiang Gao; Guangli Xiu; Tingting Hu (Science of The Total Environment, 2024)

Notes on two new species of Russula subsect. Cyanoxanthinae (Russulaceae, Russulales) from southern China - Yan-Liu Chen; Jun-Feng Liang; Sheng-Kun Wang; Bin Chen; Jin-Hua Zhang; Meng-Ya An; Xing Li; Xue-Lian Gao; Xia Chen; Jin-Peng Liao (Mycological Progress, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Underwater Object Detection Algorithm Based on an Improved YOLOv8 - Fubin Zhang; Weiye Cao; Jian Gao; Shubing Liu; Chenyang Li; Kun Song; Hongwei Wang (Journal of Marine Science and Engineering, 2024)
Due to the complexity and diversity of underwater environments, traditional object detection algorithms face challenges in maintaining robustness and detection accuracy when applied underwater. This paper proposes an underwater object detection algorithm based on an improved YOLOv8 model. First, the introduction of CIB building blocks into the backbone network, along with the optimization of the C2f structure and the incorporation of large-kernel depthwise convolutions, effectively enhances the model’s receptive field. This improvement increases the capability of detecting multi-scale objects in complex underwater environments without adding a computational burden. Next, the incorporation of a Partial Self-Attention (PSA) module at the end of the backbone network enhances model efficiency and optimizes the utilization of computational resources while maintaining high performance. Finally, the integration of the Neck component from the Gold-YOLO model improves the neck structure of the YOLOv8 model, facilitating the fusion and distribution of information across different levels, thereby achieving more efficient information integration and interaction. Experimental results show that YOLOv8-CPG significantly outperforms the traditional YOLOv8 in underwater environments. Precision and Recall show improvements of 2.76% and 2.06%. Additionally, mAP50 and mAP50-95 metrics have increased by 1.05% and 3.55%, respectively. Our approach provides an efficient solution to the difficulties encountered in underwater object detection.

ALKBH5 facilitates the progression of infantile hemangioma by increasing FOXF1 expression in a m6A-YTHDF2 dependent manner to activate HK-2 signaling - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2024)

Experimental study of sloshing flows in a rectangular tank under coupled pitch and heave excitations - Peng Peng; Zhenguo Gao; Xianshu Li; Kun Liu (Ocean Engineering, 2024)

Associations of prenatal exposure to individual and mixed organophosphate esters with ADHD symptom trajectories in preschool children: The modifying effects of maternal Vitamin D - Han Li; Juan Tong; Xing Wang; Mengjuan Lu; Fengyu Yang; Hui Gao; Hong Gan; Shuangqin Yan; Guopeng Gao; Kun Huang; Yunxia Cao; Fangbiao Tao (Journal of Hazardous Materials, 2024)

Engineering defective organic–inorganic heterojunctions as an alternative approach to precious metal modification in ultrasensitive H2S gas detection at room temperature - Rongyang Kou; Zhen-Kun He; Junhan Li; Junjian Zhao; Yan-Yan Song; Zhida Gao; Chenxi Zhao (Chemical Engineering Journal, 2024)

Fabrication of self-cleaning nanofiltration membranes through interfacial polymerization using PEI@CoPc monomer for Mg2+/Li+ separation - Yong-Sheng Li; Yi-Wei Gao; Yi-Kun Zhu; Heng Zhang; Wen-Shuang Zhang; Yong-Heng Yin; Yu-Xia Zhang; Chong-Bin Wang (Chemical Engineering Journal, 2024)

Enabling long cycle aluminum-sulfur batteries via structurally stable Co, N-doped graphene-CNTs covalently bonded hybrid - Jinsheng Lv; Guobin Lai; Tian Yang; Xiaotong Sun; Feng Liu; Wenpeng Wu; Mengfan Shi; Guantong Wang; Kun Gao; Xiangyang Li; Nan Chen (Chemical Engineering Journal, 2024)

The stress of bioactive compounds on microbes in anaerobic digestion of food waste and mitigation strategies: A critical review - Qingwei Gao; Yuhan Zhang; Lili Li; Huimin Zhou; Kun Wang; Jing Ding; Junqiu Jiang; Liangliang Wei; Qingliang Zhao (Chemical Engineering Journal, 2024)

Simultaneously enhancement of methane production and active phosphorus transformation by sludge-based biochar during high solids anaerobic co-digestion of dewatered sludge and food waste: Performance and mechanism - Zhaoxia Wang; Lili Li; Hongyuan Gao; Junqiu Jiang; Qingliang Zhao; Xinwen Li; Wangyang Mei; Qingwei Gao; Huimin Zhou; Kun Wang; Liangliang Wei (Bioresource Technology, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Experimental investigation on compressive dwell fatigue behavior of titanium alloy pressure hull for deep-sea manned submersibles - Lei Wang; Cong Ye; Chengqi Sun; Shichao Feng; Xiaozhong Xie; Yuan Gao; Kun Zhao; Yanqing Li; Zhengquan Wan (Ocean Engineering, 2024)

Comprehensive effects of salinity, dissolved organic carbon and copper on mortality, osmotic regulation and bioaccumulation of copper in Oryzias melastigma - Liang Cui; Xiaoguang Li; Yan Luo; Xiangyun Gao; Li Chen; Xubo Lv; Jiayu Peng; Hua Zhang; Kun Lei (Science of The Total Environment, 2024)

Comprehensive assessment of copper's effect on marine organisms under ocean acidification and warming in the 21st century - Liang Cui; Chen Cheng; Xiaoguang Li; Xiangyun Gao; Xubo Lv; Yan Wang; Hua Zhang; Kun Lei (Science of The Total Environment, 2024)

Ferric- and calcium-loaded red soil assist colonization of submerged macrophyte for the in-situ remediation of eutrophic shallow lake: From mesocosm experiment to field enclosure application - Wei Li; Taotao Dai; Jinfu Liu; Jiayou Zhong; Kun Wu; Guiqing Gao; Yuwei Chen; Houbao Fan (Science of The Total Environment, 2024)

Application of a coupled linear-bistable system in point absorber wave energy converter - Yu Gao; Kun Liu; Li Ke; Xiantao Zhang; Wenan Jiang; Zhenguo Gao (Ocean Engineering, 2024)

Rhombohedral platinum-copper intermetallic compound: A high phosphate tolerance electrocatalyst for HT-PEMFC - Wenrui Zhang; Sheng Xu; Yunxu Yang; Qingwei Gao; Sheng Zhu; Kun Ding; Qiaoxia Li; Penghui Shi; Yulin Min (Chemical Engineering Journal, 2024)

Association of indoor solid fuel pollution with risk factors for cardiovascular disease among Chinese adults: A nationally multi-center study - Wenming Shi; Yongzhen Li; Yonggang Huang; Guang Huang; Changbo Jin; Jie Chen; Kun Gao (Building and Environment, 2024)

Investigation on Mechanical and Failure Characteristics of Sandstone with Flaw - Zheng-Hua Gao; Qing Li; Chen Huang; Tong-De Zhao; Bing-Bing Yu; Shao-Kun Liu (Geotechnical and Geological Engineering, 2024)

Tunable vortex bound states in multiband CsV3Sb5-derived kagome superconductors - Zihao Huang; Xianghe Han; Zhen Zhao; Jinjin Liu; Pengfei Li; Hengxin Tan; Zhiwei Wang; Yugui Yao; Haitao Yang; Binghai Yan; Kun Jiang; Jiangping Hu; et al. (Science Bulletin, 2024)

Theoretical study on the interaction between SF6 and TiO2(001) surface: A DFT+U study - Yunjian Wu; Peng Gao; Yalong Li; Zhaodi Yang; Kun Wan; Xiaoxing Zhang (Journal of Fluorine Chemistry, 2024)

Effect of surface water on wollastonite carbonation: Activated dissolution and mass transfer - Tao Wang; Wenjing Tang; Wei Zhang; Zhenwei Yi; Ruonan Guo; Li Zhang; Kun Luo; WenYang Fan; Xiang Gao (Chemical Engineering Journal, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Preconditioning exercise reduces brain damage of ischemic stroke in rats via PI3K–AKT pathway by bioinformatic analysis - Kai Li; Zhen-Kun Gao; Yi-Sha Guo; Xin-Ya Shen; Yu Han; Mei Yuan; Xia Bi (Experimental Brain Research, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Nitrogen and Sulfur co-doped Carbon dots as an “on-off-on” Fluorescent Sensor for the Detection of Hg2+ and Ampicillin - LongYao Ma; ChaoQun Ma; GuoQing Chen; Jiao Gu; Taiqun Yang; Lei Li; Hui Gao; Yi Xiong; Yamin Wu; Chun Zhu; Yan Zhou; Anqi Hu; et al. (Journal of Fluorescence, 2024)

Enhanced dewaterability of food waste digestate by biochar/potassium ferrate treatments: Performance and mechanisms - Xinwen Li; Qingliang Zhao; Lili Li; Wangyang Mei; Zhaoxia Wang; Qingwei Gao; Kun Wang; Huimin Zhou; Liangliang Wei; Junqiu Jiang (Journal of Environmental Management, 2024)

Potassium isotopes as a tracer of hydrothermal alteration in ore systems - Kun-Feng Qiu; Rolf L. Romer; Zheng-Yu Long; Hao-Cheng Yu; Simon Turner; Ruo-Qi Wan; Xiao-Qiang Li; Zi-Yue Gao; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

Promoting methane production during anaerobic digestion with biochar: Is it influenced by quorum sensing? - Qingwei Gao; Qingliang Zhao; Kun Wang; Xinwen Li; Huimin Zhou; Jing Ding; Lili Li (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Heterozygosity analysis of spontaneous 2n female gametes and centromere mapping of the diploid Hevea brasiliensis based on full-sib triploid populations - Yuan-yuan Zhang; Hong-kun Li; Xiao Huang; Yu-jiao Yuan; Xiao-fei Zhang; Xin-sheng Gao; Xiang-jun Wang; Ming-ming Wei; Hua-sun Huang; Weiguo Li (Plant Reproduction, 2024)

A comprehensive review of the effects of salinity, dissolved organic carbon, pH, and temperature on copper biotoxicity: Implications for setting the copper marine water quality criteria - Liang Cui; Xiaoguang Li; Yan Luo; Xiangyun Gao; Yan Wang; Xubo Lv; Hua Zhang; Kun Lei (Science of The Total Environment, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

In-situ rooting biconical-nanorods-like Co-doped FeP @carbon architectures toward enhanced lithium storage performance - Juxin Yu; Yanyan He; Junhui Li; Caifu Dong; Yuxin Dai; Tinting Gao; Xiao Wang; Kun Yue; Guowei Zhou (Chemical Engineering Journal, 2023)

Simulated nitrogen deposition alters the ectomycorrhizal fungal community structure in northern Korean pine plantations - Gao Xiang; Ruotong Wu; Mengmeng Zhang; Kun Li; Xin He; Yu Song; Fuqiang Song (CATENA, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Unraveling the mode substitution of dockless bike-sharing systems and its determinants: A trip level data-driven interpretation - Kun Gao; Aoyong Li; Yang Liu; Jorge Gil; Yiming Bie (Sustainable Cities and Society, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Design, synthesis and biological activity determination of novel phenylpyrazole protoporphyrinogen oxidase inhibitor herbicides - Li-xia Zhao; Kun-yu Chen; Hua-yong Zhao; Yue-li Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2023)

Performance of high solids enzymatic hydrolysis and bioethanol fermentation of food waste under the regulation of saponin - Huimin Zhou; Junqiu Jiang; Qingliang Zhao; Zhaoxia Wang; Lili Li; Qingwei Gao; Kun Wang (Bioresource Technology, 2023)

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Improvement of Learning and Memory by Elevating Brain D-Aspartate in a Mouse Model of Fragile X Syndrome - Yu-Jiao Li; Kun Zhang; Ting Sun; Yan-Yan Guo; Qi Yang; Shui-Bing Liu; Yu-Mei Wu; Ming-Gao Zhao (Molecular Neurobiology, 2023)
Fragile X syndrome (FXS) is an inherited human mental retardation that arises from expansion of a CGG repeat in the Fmr1 gene, causing loss of the fragile X mental retardation protein (FMRP). It is reported that N-methyl-D-aspartate receptor (NMDAR)-mediated facilitation of long-term potentiation (LTP) and fear memory are impaired in Fmr1 knockout (KO) mice. In this study, biological, pharmacological, and electrophysiological techniques were performed to determine the roles of D-aspartate (D-Asp), a modulator of NMDAR, and its metabolizing enzyme D-aspartate oxidase (DDO) in Fmr1 KO mice. Levels of D-Asp were decreased in the medial prefrontal cortex (mPFC ); however, the levels of its metabolizing enzyme DDO were increased. Electrophysiological recordings indicated that oral drinking of D-Asp recovered LTP induction in mPFC from Fmr1 KO mice. Moreover, chronic oral administration of D-Asp reversed behavioral deficits of cognition and locomotor coordination in Fmr1 KO mice. The therapeutic action of D-Asp was partially through regulating functions of NMDARs and mGluR5/mTOR/4E-BP signaling pathways. In conclusion, supplement of D-Asp may benefit for synaptic plasticity and behaviors in Fmr1 KO mice and offer a potential therapeutic strategy for FXS.

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Abietane diterpenoids with anti-inflammatory activities from Callicarpa bodinieri - Yue Sun; Hong-Ying Yang; Pei-Zhi Huang; Lan-Jun Zhang; Wei-Jiao Feng; Ya Li; Kun Gao (Phytochemistry, 2023)

Application of nonlinear stiffness mechanism on energy harvesting from vortex-induced vibrations - Zhenguo Gao; Zhifu Li; Jianjie Niu; Qilin Yin; Kun Liu (Frontiers in Marine Science, 2023)
This study investigates the potential of vortex-induced vibration (VIV) as a renewable energy source, achieved when fluid flow interacts with a bluff body, inducing self-sustained oscillations through vortex shedding in the wake. While VIV research has traditionally focused on understanding its mechanisms and mitigating detrimental effects, interest in VIV energy harvesting has surged as a means to convert marine hydrokinetic (MHK) energy into usable electrical power. The nonlinear effects of two linear oblique springs on VIV energy harvesting are explored using the wake oscillator model, encompassing bistable and Duffing hardening stiffness. The study examines the response and energy harvesting performance while considering the impact of undeformed spring length, structural damping, and initial conditions on VIV energy conversion. Findings show that nonlinear stiffness application in the VIV system can broaden the synchronization bandwidth or reduce the VIV initiation flow speed. Bistable stiffness may broaden the synchronization velocity range, while Duffing hardening stiffness efficiently reduces the VIV initiation speed with small energy harvesting loss. Combining both stiffness types with appropriate control strategies presents a promising approach for achieving a broad synchronization VIV bandwidth and low initiation flow speed. Key parameters, such as the nondimensional parameter defining spring system obliquity and the ratio between undeformed spring length and cylinder diameter, significantly influence VIV response and energy harvesting. Moreover, optimal structural damping is vital to maximize energy harvesting efficiency, and understanding and controlling initial conditions are crucial for optimizing VIV synchronization bandwidth and energy harvesting efficiency for both bistable and Duffing hardening stiffness. This study provides valuable insights into VIV system dynamics and energy conversion potential with nonlinear springs, offering promising avenues for enhancing energy harvesting efficiency and inspiring further applications of nonlinear effects in VIV energy converters.

Structure and anti-inflammatory activity of neo-clerodane diterpenoids from Scutellaria barbata - ShuTing Li; Dan Xu; Jing Jia; Wenbo Zou; JieYing Liu; Yao Wang; Kun Zhang; Xi Zheng; Yan-Yan Ma; Xuejian Zhang; Deng-Gao Zhao (Phytochemistry, 2023)

Fluoride contents in commonly used commercial phosphate fertilizers and their potential risks in China - Hao Li; Xuzhe Ma; Xunrong Huang; Wei Ji; Kun Chen; Shaoquan Xu; Pengcheng Gao (Environmental Monitoring and Assessment, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

Insights into high-solids anaerobic digestion of food waste concomitant with sorbate: Performance and mechanisms - Qingwei Gao; Lili Li; Qingliang Zhao; Kun Wang; Huimin Zhou; Weiye Wang; Jing Ding (Bioresource Technology, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Enhancing of pretreatment on high solids enzymatic hydrolysis of food waste: Sugar yield, trimming of substrate structure - Huimin Zhou; Qingliang Zhao; Junqiu Jiang; Zhaoxia Wang; Lili Li; Qingwei Gao; Kun Wang (Bioresource Technology, 2023)

Research hotspots and trends in discovery of anticancer agents from algae: A 20-year bibliometric and visualized analysis based on Web of Science and CiteSpace - Kun Gao; Meng Zhang; Linqing Li; Mengting Yang; Qilin Zheng; Qiaoqiao Liu; Ruoxu Ning; Zheng Gao; Xiangyuan Deng (Algal Research, 2023)

Feasibility of growing microalgae on wastewaters collected from a vinegar plant for, concurrently, nutrient removal and biomass production - Zheng Gao; Kun Gao; Linqing Li; Mengting Yang; Pengfei Cheng; Qilin Zheng; Meng Zhang; Ruoxu Ning; Qiaoqiao Liu; Roger Ruan; Xiangyuan Deng (Algal Research, 2023)

Anti-inflammatory activity of phenolics from Hypericum japonicum - Xinyu Li; Dan Xu; JieYing Liu; Yan-Yan Ma; Deng-Gao Zhao; Kun Zhang (Phytochemistry Letters, 2023)

Perfluorooctane sulfonate and perfluorooctanoic acid inhibit progesterone-responsive capacitation through cAMP/PKA signaling pathway and induce DNA damage in human sperm - Lijun Shan; Yuhao Chai; Tian Gao; Kun Li; Jianmin Yu; Fei Liang; Ya Ni; Peibei Sun (Environmental Toxicology and Pharmacology, 2023)

Analytical Solutions for the Characteristic Size Distribution of the Elliptical Model in Fractured Rock Mass - Kun Xiao; Ru Zhang; Jing Xie; Li Ren; Mingzhong Gao; Zetian Zhang; Chendi Lou; Ting Ai; Ersheng Zha (Rock Mechanics and Rock Engineering, 2023)

Caveolin-1-Mediated Cholesterol Accumulation Contributes to Exaggerated mGluR-Dependent Long-Term Depression and Impaired Cognition in Fmr1 Knockout Mice - Li Luo; Le Yang; Kun Zhang; Shi-Meng Zhou; Yan Wang; Liu-Kun Yang; Bin Feng; Shui-Bing Liu; Yu-Mei Wu; Ming-Gao Zhao; Qi Yang (Molecular Neurobiology, 2023)
Fragile X syndrome (FXS) is one of the most common inherited mental retardation diseases and is caused by the loss of fragile X mental retardation protein (FMRP) expression. The metabotropic glutamate receptor (mGluR) theory of FXS states that enhanced mGluR-dependent long-term depression (LTD) due to FMRP loss is involved in aberrant synaptic plasticity and autistic-like behaviors, but little is known about the underlying molecular mechanism. Here, we found that only hippocampal mGluR-LTD was exaggerated in adolescent Fmr1 KO mice, while N-methyl-D-aspartate receptor (NMDAR)-LTD was intact in mice of all ages. This development-dependent alteration was related to the differential expression of caveolin-1 (Cav1), which is essential for caveolae formation. Knockdown of Cav1 restored the enhanced mGluR-LTD in Fmr1 KO mice. Moreover, hippocampal Cav1 expression in Fmr1 KO mice induced excessive endocytosis of the α-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate (AMPA) receptor subunit GluA2. This process relied on mGluR1/5 activation rather than NMDAR. Interference with Cav1 expression reversed these changes. Furthermore, massive cholesterol accumulation contributed to redundant caveolae formation, which provided the platform for mGluR-triggered Cav1 coupling to GluA2. Importantly, injection of the cholesterol scavenger methyl-β-cyclodextrin (Mβ-CD) recovered AMPA receptor trafficking and markedly alleviated hyperactivity, hippocampus-dependent fear memory, and spatial memory defects in Fmr1 KO mice. Together, our findings elucidate the important role of Cav1 in mediating mGluR-LTD enhancement and further inducing AMPA receptor endocytosis and suggest that cholesterol depletion by Mβ-CD during caveolae formation may be a novel and safe strategy to treat FXS.

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Anti-inflammatory activities of triterpenoids from Euphorbia humifusa Willd - Pei-Zhi Huang; Hong-Ying Yang; Lan-Jun Zhang; Yue Sun; Ya Li; Kun Gao (Phytochemistry Letters, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

High efficiency activation of peroxydisulfate by an Fe3O4@PDAn-CuxO core–shell composite for triclosan degradation: The role of oxygen vacancy - Shuai Shao; Xiaoshuai Li; Zhimin Gong; Bo Fan; Mengjie Wang; Jianbiao Peng; Kun Lu; Shixiang Gao (Chemical Engineering Journal, 2023)

Effects of different rapid cooling temperatures and annealing on functional properties of starch straws after thermoplastic extrusion - Kun Wang; Feixue Zou; Haiteng Tao; Wei Gao; Li Guo; Bo Cui; Chao Yuan; Pengfei Liu; Lu Lu; Zhengzong Wu (Carbohydrate Polymers, 2023)

Deciphering the fate of osmotic stress priming on enhanced microorganism acclimation for purified terephthalic acid wastewater treatment with high salinity and organic load - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Bioresource Technology, 2023)

High plant species diversity enhances lignin accumulation in a subtropical forest of southwest China - Zongyao Qian; Rui Gu; Kun Gao; Dejun Li (Science of The Total Environment, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Fluoride accumulation characteristics in a northern China apple orchard that has had long-term phosphate fertilization - Xunrong Huang; Hao Li; Xuzhe Ma; Wei Ji; Kun Chen; Bingnian Zhai; Pengcheng Gao (Science of The Total Environment, 2023)

Biomimetic platinum forest enables 3D micro-supercapacitors with enhanced areal performance - Panpan Zhang; Yang Li; Mingming Gao; Sheng Yang; Mingchao Wang; Zaichun Liu; Kun Guo; Faxing Wang; Xing Lu (Chemical Engineering Journal, 2023)

NiFe2V2O8@N-Doped carbon Yolk-Double shell spheres for efficient lithium storage - Chenyu Yang; Xiao Wang; Yongqiang Ren; Shaonan Gu; Qian Wang; Huan Li; Kun Yue; Tingting Gao; Guowei Zhou (Chemical Engineering Journal, 2023)

The association between early pregnancy exposure to green space and maternal glucolipid metabolism disorders: evaluation of the mediating role of serum 25-hydroxyvitamin D - Wenjie Yu; Yingqing Li; Kangdi Zhang; Xinqiang Wang; Jie Wang; Xin Cheng; Zhenhua Li; Yicheng Mao; Jiawen Zhao; Tao Li; Maolin Chen; Guopeng Gao; et al. (Environmental Science and Pollution Research, 2023)

Temperature-regulated and starvation-induced refractory para-toluic acid anaerobic biotransformation - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Does anaerobic digestion improve environmental and economic benefits of sludge incineration in China? Insight from life-cycle perspective - Shunan Zhao; Kun Yan; Zhihui Wang; Yong Gao; Kun Li; Jianfeng Peng (Resources, Conservation and Recycling, 2023)

Charge instability of topological Fermi arcs in chiral crystal CoSi - Zhicheng Rao; Quanxin Hu; Shangjie Tian; Qing Qu; Congrun Chen; Shunye Gao; Zhenyu Yuan; Cenyao Tang; Wenhui Fan; Jierui Huang; Yaobo Huang; Li Wang; et al. (Science Bulletin, 2023)

Evaluating the dynamic distribution process and potential exposure risk of chlorinated paraffins in indoor environments of Beijing, China - Lu Bai; Kun Lv; Juan Li; Wei Gao; Chunyang Liao; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Height aware understanding of remote sensing images based on cross-task interaction - Yingchao Feng; Xian Sun; Wenhui Diao; Jihao Li; Ruigang Niu; Xin Gao; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Numerical simulation of microchannel flow boiling and critical heat flux under rolling motion - Zhen Tian; Kun Li; Yuan Zhang; Zhikang Huang; Shuming Xu; Wenzhong Gao (International Journal of Refrigeration, 2023)

MOF-derived CoNC@rGO/amine-rich@rGO/fluorinated-epoxy nanocomposites with EMI shielding, mechanical robustness, superamphiphobicity and long-term anticorrosion properties - Kun Li; Liuwenlin Han; Xiaomu Wang; Feng Gao; Junying Zhang; Jue Cheng (Chemical Engineering Journal, 2023)

Disruption of transcription factor RhMYB123 causes the transformation of stamen to malformed petal in rose (Rosa hybrida) - Kun Li; Yuqi Li; Yi Wang; Yonghong Li; Junna He; Yunju Li; Lisi Du; Yuerong Gao; Nan Ma; Junping Gao; Xiaofeng Zhou (Plant Cell Reports, 2022)

Comprehensive insights into the influence of supplemental green light on the photosynthesis of ginger (Zingiber officinale Roscoe) - Xue Lv; Song Gao; Na Li; Yao Lv; Zijing Chen; Bili Cao; Kun Xu (Protoplasma, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

A critical review of experimental and CFD techniques to characterize the mixing performance of anaerobic digesters for biogas production - Lili Li; Kun Wang; Qingliang Zhao; Qingwei Gao; Huimin Zhou; Junqiu Jiang; Wangyang Mei (Reviews in Environmental Science and Bio/Technology, 2022)

Accurate detection method of high-density polyethylene film leakage location based on secondary electric potential difference - Fu-Yu Jiang; Pei-Xuan Qiao; Li-Kun Gao; Hai-Jun Chen (Applied Geophysics, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Influence of nitrogen wet deposition on nitrogen output in a typical watershed in the Three Gorges Reservoir Area - Chen-dong Lu; Liu-yi Zhang; Kun Yan; Yu-kuan Wang; Shan-gao Xiong; Chen-tao Huang; Ting-zhen Li; Mao-fei Ni (Journal of Mountain Science, 2022)

Correction to: Short‑term effects of gaseous air pollutants on outpatient visits for respiratory diseases: a case‑crossover study in Baotou, China - Hao‑Yu Gao; Xiao‑Ling Liu; Ya‑Ke Lu; Yu‑Hong Liu; Li‑Kun Hu; Yan‑Ling Li; Xiao‑Dong Feng; Yu‑Xiang Yan (Environmental Science and Pollution Research, 2022)

Short-term effects of gaseous air pollutants on outpatient visits for respiratory diseases: a case-crossover study in Baotou, China - Hao-Yu Gao; Xiao-Ling Liu; Ya-Ke Lu; Yu-Hong Liu; Li-Kun Hu; Yan-Ling Li; Xiao-Dong Feng; Yu-Xiang Yan (Environmental Science and Pollution Research, 2022)

Effect of absolute humidity on influenza activity across different climate regions in China - Li Qi; Tian Liu; Yuan Gao; Qin Li; Wenge Tang; Dechao Tian; Kun Su; Yu Xiong; Jun Yang; Luzhao Feng; Qiyong Liu (Environmental Science and Pollution Research, 2022)

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

Mercury distribution and emission reduction potentials of Chinese coal-fired industrial boilers - Yali Tong; Kun Wang; Jiajia Gao; Tao Yue; Penglai Zuo; Chenlong Wang; Li Tong; Xiaoxi Zhang; Yun Zhang; Quanming Liang; Jieyu Liu (Air Quality, Atmosphere & Health, 2022)

Four new triterpene glucosides from Salacia cochinchinensis Lour - Lu Gao; Li-Kun Duan; Jin-E Feng; Yun-Tao Jiang; Jun Gao; Jun-Ting Fan; Rong Dai; Zhi-Yong Jiang (Natural Product Research, 2022)

Carbon budget and balance critical processes of the regional land-water-air interface: Indicating the earth system’s carbon neutrality - Yang Gao; Shuoyue Wang; Yao Lu; Jianbao Liu; Sidan Lyu; Kun Sun; Junjie Jia; Zhaoxi Li; Guirui Yu (Science China Earth Sciences, 2022)

ALKBH5 promotes the progression of infantile hemangioma through regulating the NEAT1/miR-378b/FOSL1 axis - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2022)

Design, synthesis and fungicidal activity of 3,4-dichloroisothiazolocoumarin-containing strobilurins - You Lv; Kun Li; Wei Gao; Zesheng Hao; Weibo Wang; Xiaoyu Liu; Liangfu Tang; Zhijin Fan (Molecular Diversity, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Triterpenoids and lignans from Schisandra chinensis and their inhibition activities of Cdc25A/B phosphatases - Qian-Qian Zhao; Wen-Jun Wei; Ya Li; Kun Gao (Natural Product Research, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Strategy for the construction of a core collection for Pinus yunnanensis Franch. to optimize timber based on combined phenotype and molecular marker data - Xiaoli Wang; Zilin Cao; Chengjie Gao; Kun Li (Genetic Resources and Crop Evolution, 2021)

Explanation of heavy metal pollution in coal mines of china from the perspective of coal gangue geochemical characteristics - Huadong Gao; Yanli Huang; Wei Li; Junmeng Li; Shenyang Ouyang; Tianqi Song; Fengyuan Lv; Wen Zhai; Kun Ma (Environmental Science and Pollution Research, 2021)

Different responses of two Chinese cabbage (Brassica rapa L. ssp. pekinensis) cultivars in photosynthetic characteristics and chloroplast ultrastructure to salt and alkali stress - Na Li; Zhihuan Zhang; Song Gao; Yao Lv; Zijing Chen; Bili Cao; Kun Xu (Planta, 2021)

Effect of Coformer Selection on In Vitro and In Vivo Performance of Adefovir Dipivoxil Cocrystals - Luyuan Li; Zunting Pang; Kun Ma; Yuan Gao; Daoyi Zheng; Yuanfeng Wei; Jianjun Zhang; Shuai Qian (Pharmaceutical Research, 2021)

Advances in genetic studies of black point disease in wheat - Qiao-Yun Li; Chuang Gao; Yang-Kun Li (Journal of Plant Diseases and Protection, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

Sediment carbon short-term response to water carbon content change in a large floodplain-lake system - Zhaoxi Li; Yang Gao; Junjie Jia; Kun Sun; Sidan Lyu; Shuoyue Wang; Yao Lu; Xuefa Wen (Environmental Science and Pollution Research, 2021)

Experimental study on adsorption promotion and desorption restrain of gas-containing coal in low-temperature environment - Fakai Wang; Xuelong Li; Bo Cui; Jian Hao; Xin Gao; Kun Long; Peng Chen; Sheng Wang (Arabian Journal of Geosciences, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Biomonitoring of heavy metal contamination with roadside trees from metropolitan area of Hefei, China - Ting Fang; Ting Jiang; Kun Yang; Jing Li; Yangyang Liang; Xiuxia Zhao; Na Gao; Hui Li; Wenxuan Lu; Kai Cui (Environmental Monitoring and Assessment, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

Anxiolytic Effects of 8-O-Acetyl Shanzhiside Methylester on Acute and Chronic Anxiety via Inflammatory Response Inhibition and Excitatory/Inhibitory Transmission Imbalance - Ting Sun; Li Luo; Qin-Qin Tian; Wen-Ju Wang; Qing-Qing Liu; Le Yang; Kun Zhang; Wei Zhang; Ming-Gao Zhao; Qi Yang (Neurotoxicity Research, 2020)
Anxiety leads to a global decline in quality of life and increase in social burden. However, treatments are limited, because the molecular mechanisms underlying complex emotional disorders are poorly understood. We explored the anxiolytic effects of 8-O-acetyl shanzhiside methylester (8-OaS), an active component in Lamiophlomis rotata ( L . rotata ; Benth.) or Kudo, a traditional herb that has been shown to be effective in the clinical treatment of chronic pain syndromes in China. Two mouse anxiety models were used: forced swimming stress (FSS)–induced anxiety and complete Freund’s adjuvant (CFA)–induced chronic inflammatory pain. All animal behaviors were analyzed on the elevated plus maze and in the open-field test. 8-OaS significantly ameliorated anxiety-like behaviors in both anxiety models and inhibited the translation enhancement of GluN2A, GluN2B, and PSD95. Moreover, a reduction in GABA receptors disrupted the excitatory/inhibitory (E/I) balance in the basolateral amygdala (BLA), indicated by increased excitatory and decreased inhibitory presynaptic release. 8-OaS also blocked microglia activation and reduced the phosphorylation of p38, c-Jun N-terminal kinase (JNK), NF-κB p65, and tumor necrosis factor alpha (TNF-α) in the BLA of anxiety mice. 8-OaS exhibits obvious anxiolytic effects by regulating the excitatory/inhibitory (E/I) synaptic transmission and attenuating inflammatory responses in the BLA.

Grain quality variations from year to year among the Chinese genotypes - Sheng Kun; Yang Lijuan; Li Xiaohang; Gao Yang; Jiang Zhikai; Duan Aiwang (Cereal Research Communications, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Research on intelligent prediction and zonation of basin-scale flood risk based on LSTM method - Minzhi Yang; Ping-an Zhong; Jieyu Li; Weifeng Liu; Yinghui Li; Kun Yan; Yinyang Yuan; Yihui Gao (Environmental Monitoring and Assessment, 2020)

A DTW distance-based seismic waveform clustering method for layers of varying thickness - Zhong Hong; Kun-Hong Li; Ming-Jun Su; Guang-Min Hu; Jun Yang; Gai Gao; Bin Hao (Applied Geophysics, 2020)

Development and validation of a rapid kit for authenticity of murine meat in meat products with a species-specific PCR assay - Siqi Duan; Jin Xia Ai; Liyuan Sun; Lijun Gao; Mingcheng Li; Kun Chen; Dan Li (Food Additives & Contaminants: Part A, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Enhanced stability of a rumen-derived xylanase using SpyTag/SpyCatcher cyclization - Ye-Bo Zhou; Jia-Wen Cao; Xiao-Bao Sun; Huan Wang; De-Ying Gao; Yang-Nan Li; Kai-Yue Wu; Jia-Kun Wang; Guo-Ying Qian; Qian Wang (World Journal of Microbiology and Biotechnology, 2020)

Smart calcium peroxide with self-sufficience for biomedicine - Shutao Gao; Miao Fan; Zhenhua Li; Kun Ge; Xing-Jie Liang; Jinchao Zhang (Science China Life Sciences, 2020)

Genetic diversity analysis of Tibetan turnip(Brassica rapa L. ssp. rapifera Matzg) revealed by morphological, physiological, and molecular marker - Yingying Gao; Wenfeng Gong; Rongrong Li; Lei Zhang; Yanlin Zhang; Yongbin Gao; Jie Lang; Kun Zhao; Kaiwen Liu; Xiaolin Yu (Genetic Resources and Crop Evolution, 2020)

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Journal of Biogeography, 2019)
Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We sampled plant species along a 1,200 m elevational gradient across forest strata (trees, shrubs and herbs) at different spatial scales (neighbourhood and community). We integrated phylogenetic and functional diversity to disentangle the roles of ecological mechanisms in structuring community assembly. We also determined the relative effects of climatic, soil and biotic variables and their interactions on these community assemblages. Results The phylogenetic and functional diversity of trees were lower at the extremes of the elevational gradient, where they were constrained by water availability or temperature. While communities with higher species diversity exhibited an overdispersed structure at mid‐elevations. For shrubs, overdispersion was exhibited at high elevations despite low species richness, which could be consistent with facilitative interactions or competition exclusion. However, most communities of herbs appear to have a markedly random structure, despite some incongruence between phylogenetic divergence and functional convergence, as well as influences from overstorey trees and local light conditions. The relative effects of abiotic variables on community structure were larger at the community scale than at the neighbourhood scale. Main conclusions Our study emphasises the importance of considering phylogenies and traits in understanding the strata‐ and scale‐dependent mechanisms of forest community assembly. Collectively, results indicate that contrasting assembly mechanisms interact across different strata along elevational gradients to shape diverse forest communities.

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

Two pairs of phenolic enantiomers from the leaves of Eucommia ulmoides Oliver - Jian-Kun Yan; Xu-Liu Shi; Paul Owusu Donkor; Xiu-Mei Gao; Li-Qin Ding; Feng Qiu (Natural Product Research, 2019)

Structures and antipathogenic fungi activities of flavonoids from pathogen-infected Astragalus adsurgens - Ya Li; Wenjun Wei; Jiwen Zhang; Guangda Li; Kun Gao (Natural Product Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Small UAV based multi-viewpoint image registration for monitoring cultivated land changes in mountainous terrain - Fei Song; Mengya Li; Yang Yang; Kun Yang; Xueyan Gao; Tingting Dan (International Journal of Remote Sensing, 2018)

A pair of enantiomeric 5-oxabicyclic[4.3.0]lactam derivatives and one new polyketide from the marine-derived fungus Penicillium griseofulvum - Jian-Kun Yang; Bin Zhang; Tong Gao; Meng-Yue Yang; Guo-Zheng Zhao; Hua-Jie Zhu; Li Liu; Fei Cao (Natural Product Research, 2018)

Quantitative contribution of Cd2+ adsorption mechanisms by chicken-manure-derived biochars - Fei Huang; Li-Yang Gao; Jin-Huan Deng; Shao-Hua Chen; Kun-Zheng Cai (Environmental Science and Pollution Research, 2018)

Antibacterial Activity of Hydroxytyrosol Acetate from Olive Leaves ( Olea Europaea L.) - Jianteng Wei; Shuxian Wang; Dong Pei; Liangjing Qu; Ya Li; Jianjun Chen; Duolong Di; Kun Gao (Natural Product Research, 2018)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Colony formation by the green alga Chlorella vulgaris in response to the competitor Ceratophyllum demersum - Jing Dong; Yunni Gao; Mengyang Chang; Hanhui Ma; Kun Han; Xin Tao; Yan Li (Hydrobiologia, 2018)

Silicon-mediated changes in radial hydraulic conductivity and cell wall stability are involved in silicon-induced drought resistance in tomato - Bi-li Cao; Lili Wang; Song Gao; Jie Xia; Kun Xu (Protoplasma, 2017)

Identifying late Carboniferous sanukitoids in Hala’alate Mountain, Northwest China: new constraint on the closing time of remnant ocean basin in West Junggar - Gan-Yu Li; Yong-Jun Li; Xuan-Ce Wang; Gao-Xue Yang; Ran Wang; Kun-Peng Xiang; Jia Liu; Li-Li Tong (International Geology Review, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Warm–cold colonization: response of oaks to uplift of the Himalaya–Hengduan Mountains - Hong‐Hu Meng; Tao Su; Xiao‐Yang Gao; Jie Li; Xiao‐Long Jiang; Hang Sun; Zhe‐Kun Zhou (Molecular Ecology, 2017)
Clarifying the relationship between distribution patterns of organisms and geological events is critical to understanding the impact of environmental changes on organismal evolution. Quercus sect. Heterobalanus is now distributed across the Himalaya–Hengduan Mountains ( HHM ) and warm lowland in East China, yet how the distribution patterns of this group changed in response to the HHM uplift remains largely unknown. This study examines the effect of tectonic events in the HHM region on the oaks, providing a biological perspective on the geological history of this region. Fifty‐six populations of Quercus sect. Heterobalanus were genotyped using four chloroplast DNA regions and nine nuclear simple sequence repeat loci to assess population structure and diversity, supplemented by molecular dating and ancestral area reconstructions. The underlying demographic dynamics were compared using ecological niche models of the species distributions during the last glacial maximum and the present. These analyses illustrate that Quercus sect. Heterobalanus diversified as the HHM uplifted and climatic cooling during the mid‐Miocene, colonizing the cold habitats from warm broadleaf mixed forests. Lineages in cold highlands and warm lowlands have diverged as a consequence of local adaptation to diverging climates since the late Miocene. Our results suggest that continuous uplift of the HHM in the late Miocene to early Pliocene accompanied by simultaneous cooling triggered the differentiation of oaks. The biogeography of Quercus sect. Heterobalanus illuminates the geological events responsible for the modern‐day HHM .

Estrogen-like neuroprotection of isopsoralen against spinal cord injury through estrogen receptor ERα - Xiao-ming Li; Qi Yang; Xu-bo Li; Qiang Cheng; Kun Zhang; Jing Han; Jian-ning Zhao; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

NMR-Based Metabolomics Reveal a Recovery from Metabolic Changes in the Striatum of 6-OHDA-Induced Rats Treated with Basic Fibroblast Growth Factor - Hong Zheng; Liangcai Zhao; Huanhuan Xia; Cuicui Xu; Dan Wang; Kun Liu; Li Lin; Xiaokun Li; Zhihan Yan; Hongchang Gao (Molecular Neurobiology, 2016)

Characterization of eleven microsatellite markers for the tea geometrid Ectropis obliqua (Lepidoptera: Geometridae) - Shengli Jing; Baoxiao Zheng; Li Qiao; Kun Zhang; Gaoyang Chen; Shunqin Guo; Xiaoyan Huang; Yanping Gao; Lili Zhang; Hongyu Yuan (Applied Entomology and Zoology, 2016)

The inulin-type oligosaccharides extract from morinda officinalis, a traditional Chinese herb, ameliorated behavioral deficits in an animal model of post-traumatic stress disorder - Zhi-Kun Qiu; Chun-Hui Liu; Zhuo-Wei Gao; Jia-Li He; Xu Liu; Qing-Lan Wei; Ji-Sheng Chen (Metabolic Brain Disease, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

Silibinin Prevents Autophagic Cell Death upon Oxidative Stress in Cortical Neurons and Cerebral Ischemia-Reperfusion Injury - Min Wang; Yu-Jiao Li; Yi Ding; Hui-Nan Zhang; Ting Sun; Kun Zhang; Le Yang; Yan-Yan Guo; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2016)

Identification and Functional Analysis of the NADK Gene Family in Wheat - Xiang Wang; Wen-Yan Li; Mao-Mao Zhang; Yin-Tao Gao; Wen-Ting Liu; Wen-Qiang Li; Izhar Muhammad; Kun-Ming Chen (Plant Molecular Biology Reporter, 2016)

Seroprevalence of Bluetongue virus in domestic yaks (Bos grunniens) in Tibetan regions of China based on circulating antibodies - Jiakui Li; Kun Li; Muhammad Shahzad; Zhaoqing Han; Fazul Nabi; Jianfeng Gao; Jinmei Han (Tropical Animal Health and Production, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Fish consumption and n-3 polyunsaturated fatty acids, and risk of hepatocellular carcinoma: systematic review and meta-analysis - Min Gao; Kai Sun; Mujie Guo; Hang Gao; Kun Liu; Cuicui Yang; Sheng Li; Ning Liu (Cancer Causes & Control, 2015)

Transcriptome Profiling Identified Multiple Jasmonate ZIM-Domain Proteins Involved in the Regulation of Alkaloid Biosynthesis in Tobacco BY-2 Cells - Yuping Yang; Jing Guo; Pengcheng Yan; Yunshuang Li; Kun Liu; Ping Gao; Heping Zhao; Yubao Chen; Yingdian Wang; Michael P. Timko; Shengcheng Han (Plant Molecular Biology Reporter, 2015)

Genome-wide investigation of genetic changes during modern breeding of Brassica napus - Nian Wang; Feng Li; Biyun Chen; Kun Xu; Guixin Yan; Jiangwei Qiao; Jun Li; Guizhen Gao; Ian Bancroft; Jingling Meng; Graham J. King; Xiaoming Wu (Theoretical and Applied Genetics, 2014)

Differential necrotic lesion formation in soybean cultivars in response to soybean mosaic virus - Kai Zhang; Ying Pei Song; Yu Wang; Kai Li; Le Gao; Yong Kun Zhong; A. Karthikeyan; Hai Jian Zhi (European Journal of Plant Pathology, 2014)

Evaluation of yield and agronomic traits and their genetic variation in 488 global collections of Brassica napus L. - Biyun Chen; Kun Xu; Jun Li; Feng Li; Jiangwei Qiao; Hao Li; Guizhen Gao; Guixin Yan; Xiaoming Wu (Genetic Resources and Crop Evolution, 2014)

Potential health impact and genotoxicity analysis of drinking source water from Liuxihe Reservoir (P.R. China) - Weili Wang; Mei Li; Yibin Cui; Xiangyu Gao; Kun Chen; Xin Qian (Ecotoxicology, 2014)

Application of T-DNA activation tagging to identify glutamate receptor-like genes that enhance drought tolerance in plants - Guihua Lu; Xiping Wang; Junhua Liu; Kun Yu; Yang Gao; Haiyan Liu; Changgui Wang; Wei Wang; Guokui Wang; Min Liu; Guanfan Mao; Binfeng Li; et al. (Plant Cell Reports, 2014)

Imposex effects on the veined rapa whelk (Rapana venosa) in Bohai Bay, China - Li-hui An; Yanqiang Zhang; Shuang-shuang Song; Yue Liu; Zi-cheng Li; Hao Chen; Xing-ru Zhao; Kun Lei; Junmin Gao; Bing-hui Zheng (Ecotoxicology, 2013)

Complete chloroplast genome sequence of Magnolia grandiflora and comparative analysis with related species - XiWen Li; HuanHuan Gao; YiTao Wang; JingYuan Song; Robert Henry; HeZhen Wu; ZhiGang Hu; Hui Yao; HongMei Luo; Kun Luo; HongLin Pan; ShiLin Chen (Science China Life Sciences, 2013)

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

High prevalence of Eimeria infection in dairy goats in Shaanxi province, northwestern China - Guang Hui Zhao; Li-Hui Lei; Chuan-Chuan Shang; Man Gao; Yan Qing Zhao; Chao-Xi Chen; De-Kun Chen (Tropical Animal Health and Production, 2012)

Edge enhancement of gravity anomalies and gravity gradient tensors using an improved small sub-domain filtering method - Fu-Yu Jiang; Li-Kun Gao (Applied Geophysics, 2012)

Expression, Purification, and Secondary Structure Prediction of Pentatricopeptide Repeat Protein RF1A from Rice - Wang Kun; Gao Feng; Zhu Renshan; Li Shaoqing; Zhu Yingguo (Plant Molecular Biology Reporter, 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Genetic Diversity and Identity of Chinese Loquat Cultivars/Accessions (Eriobotrya japonica) Using Apple SSR Markers - Qiao He; Xiong Wei Li; Guo Lu Liang; Kun Ji; Qi Gao Guo; Wei Min Yuan; Gen Zhi Zhou; Kun Song Chen; W. Eric van de Weg; Zhong Shan Gao (Plant Molecular Biology Reporter, 2011)

Using FAM labeled DNA oligos to do RNA electrophoretic mobility shift assay - Kun Wang; Ya Gao; Xiaojue Peng; Guohua Yang; Feng Gao; Shaoqing Li; Yingguo Zhu (Molecular Biology Reports, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Role of PKCβ in hepatocellular carcinoma cells migration and invasion in vitro: a potential therapeutic target - Kun Guo; Yan Li; Xiaonan Kang; Lu Sun; Jiefeng Cui; Dongmei Gao; Yinkun Liu (Clinical & Experimental Metastasis, 2009)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

Multi-year simulations and experimental seasonal predictions for rainy seasons in China by using a nested regional climate model (RegCM_NCC). Part I: Sensitivity study - Yihui Ding; Xueli Shi; Yiming Liu; Yan Liu; Qingquan Li; Yongfu Qian; Manqian Miao; Guoqing Zhai; Kun Gao (Advances in Atmospheric Sciences, 2006)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

The MYB Transcription Factor Superfamily of Arabidopsis: Expression Analysis and Phylogenetic Comparison with the Rice MYB Family - Chen Yanhui; Yang Xiaoyuan; He Kun; Liu Meihua; Li Jigang; Gao Zhaofeng; Lin Zhiqiang; Zhang Yunfei; Wang Xiaoxiao; Qiu Xiaoming; Shen Yunping; Zhang Li; et al. (Plant Molecular Biology, 2006)